The Giant Radio Array for Neutrino Detection (GRAND): Present and Perspectives - Fang, Ke (2017)
The Giant Radio Array for Neutrino Detection (GRAND) aims at detecting ultra-high energy extraterrestrial neutrinos via the extensive air showers induced by the decay of tau leptons created in the interaction of neutrinos under the Earth?s surface. Consisting of an array of ∼ 1E5 radio antennas deployed over ∼ 2E5 km2, GRAND plans to reach, for the first time, an all-flavor sensitivity of ∼ 1.5E−10 GeV cm−2s−1 sr−1 above 5×1017 eV and a sub-degree angular resolution, beyond the reach of other planned detectors. We describe here preliminary designs and simulation results, plans for the ongoing, staged approach to the construction of GRAND, and the rich research program made possible by GRAND?s design sensitivity and angular resolution.